EVALUATION OF CAPACITY AND LEVEL OF SERVICE FOR URBAN ARTERIAL ROAD UNDER MIXED TRAFFIC CONDITIONS - A CASE STUDY OF OBA ADESIDA ROAD AKURE, NIGERIA - Ayeni, Tosin Samuel; Iyeke, Solomon (Journal of Civil Engineering, Science and Technology, 2024)
The research focused on evaluating the capacity and level of service of an urban arterial road under mixed traffic conditions and subsequently proposed traffic improvement measures. Oba Adesida Road in Akure was selected as a case study using purposive sampling. The field traffic characteristics survey employed both video-graphic technology and manual techniques, conducted from 7:00 am to 7:00 pm for seven days (Monday to Sunday). The passenger car unit equivalent (PCU) technique, utilizing the British standard method and PCU factors for each vehicle class, was applied to determine the actual volume of vehicles on the study road. Statistical calculations, including mean, median, range, and skewness, were performed using various formulas for each element. The level of service (LOS) for the study road was determined using the volume/capacity ratio through both theoretical capacity and the technical standard method. The results revealed high congestion on the study road, with traffic volumes ranging from 1080 to 2221 PCU/hr and 13,908 to 25,788 PCU/day. Throughout the week, incoming flow exceeded outbound traffic, and the road exhibited poor operating conditions during peak hours. LOS varied from C to F (LOS-C to F) when using the ratio of theoretical maximum capacity to actual volume technique. However, LOS-F was consistently observed during peak hours throughout the week when employing the technical standard method. To address these challenges, the study suggests implementing traffic management strategies, including the construction and installation of efficient traffic signals. Strict enforcement of proper use of existing bus shelters at designated stops is recommended, and the introduction of alternative urban transportation modes, such as metros and trains, supporting mass movement, should be considered, drawing inspiration from major urban cities worldwide.